Maskulinitas Gaya Dan Karakter Tari Remo Sri Utami - Tri Rusianingsih (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2022)
Rebellion against the function and role of women in dance has given rise to cases of transgender and travesti. The role of men in dance activities was gradually replaced by women. Women no longer only act as presenters in performances, but also place themselves in the status of choreographers in a work. This study aims to describe the choreograph structure, style and character of the Remo Sri Utami dance moves. To identify and analyze various data findings in the field, the study uses the concept of masculinity as well as style and character. Research that uses descriptive qualitative method with masculinity style and character approach, focuses more on data collection techniques by observation, interviews, literature studies and documentation through triangulation techniques. Aspects of motivation, spontaneous instincts, honesty, respect for self-potential, as well as cross-value experiences in art are strong reflections to form the masculinity of the Sri Utami style Remo dance.